If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-13x) + 7(2x + -2) + -13 = 0 Reorder the terms: (-13x) + 7(-2 + 2x) + -13 = 0 (-13x) + (-2 * 7 + 2x * 7) + -13 = 0 (-13x) + (-14 + 14x) + -13 = 0 Reorder the terms: -14 + -13 + (-13x) + 14x = 0 Combine like terms: -14 + -13 = -27 -27 + (-13x) + 14x = 0 Combine like terms: (-13x) + 14x = 1x -27 + 1x = 0 Solving -27 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 1x = 0 + 27 Combine like terms: -27 + 27 = 0 0 + 1x = 0 + 27 1x = 0 + 27 Combine like terms: 0 + 27 = 27 1x = 27 Divide each side by '1'. x = 27 Simplifying x = 27
| (13xX)+(87*Y)=185 | | -12h+39=-4d-17 | | 170+0.15x=c | | 4+8x=5x-25 | | -148-6x=95+3x | | y=5x+270 | | -7-7(-3+x)+6x=23 | | 7x+7=3x+6 | | -4n=17 | | 6n+4+2n=23 | | 3sinx-5cosx=8 | | 3+4(x+1)=7x | | 7-2x^3=0 | | =5(3x) | | -18.5+5y=-3(3.5Y-5.5) | | 6x-12+4x-1=-x-7+12 | | 2x+2=3-3x | | c=170+.15x | | 20=2x+5 | | 2x-5(x-4)=18 | | 20t+35=6t | | 55.847-26= | | 1x+2x=3y | | 9n=6n+27 | | 25=34-x | | 3x+6+5=2-x | | 8-1m-3m=16 | | 8x+4=6-x | | 7n+5+2n=12 | | 9(x+3)=10(1+2) | | 0.3x-2.3=2.4x+1.8 | | 4.6+(-5.9)= |